2014
DOI: 10.1021/la500377w
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Adsorption and Adsorption Hysteresis of a Thermoresponsive Diblock Copolymer

Abstract: A nonionic-cationic diblock copolymer, poly(2-isopropyl-2-oxazoline)60-b-poly((3-acrylamidopropyl)trimethylammonium chloride)17, (PIPOZ60-b-PAMPTMA17), was utilized to electrostatically tether temperature-responsive PIPOZ chains to silica surfaces by physisorption. The effects of polymer concentration, pH, and temperature on adsorption were investigated using quartz crystal microbalance with dissipation monitoring and ellipsometry. The combination of these two techniques allows thorough characterization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 46 publications
(108 reference statements)
3
24
0
Order By: Relevance
“…Claesson et al demonstrated that the adsorption of a block copolymer of PiPrOx as themoresponsive block and poly (3-acrylamidopropyltrimethylammonium chloride) as charged block to adsorb onto a negatively charged silica substrate is indeed temperature dependent. 97 Upon increasing the temperature, the PiPrOx is partially dehydrated and becomes more hydrophobic which favors the adsorption process leading to an increase in adsorbed mass. This process was found to be reversible and decreasing the temperature led to partial desorption of the block copolymer.…”
Section: Thermoresponsive Polyamides or Polymeric Amidesmentioning
confidence: 99%
“…Claesson et al demonstrated that the adsorption of a block copolymer of PiPrOx as themoresponsive block and poly (3-acrylamidopropyltrimethylammonium chloride) as charged block to adsorb onto a negatively charged silica substrate is indeed temperature dependent. 97 Upon increasing the temperature, the PiPrOx is partially dehydrated and becomes more hydrophobic which favors the adsorption process leading to an increase in adsorbed mass. This process was found to be reversible and decreasing the temperature led to partial desorption of the block copolymer.…”
Section: Thermoresponsive Polyamides or Polymeric Amidesmentioning
confidence: 99%
“…Examples of hydrophobic blocks employed include poly­(ethylene), poly­(2-(4-( tert -butoxycarbonyl)­amino)­butyl-2-oxazoline), and poly­(ferrocenyl­dimethylsilane). , Stoichiometric mixtures in water of two oppositely charged diblock ionomers, such as the PiPOx- b -poly­( l -lysine)/PiPOx- b -poly­(aspartic acid) pair, also assemble in water, forming core–corona polyion complex (PIC) micelles first reported by Kataoka . Dihydrophilic block copolymers are also of interest, in which the PiPOx block is linked to another water-soluble block, which may be thermoresponsive. …”
Section: Introductionmentioning
confidence: 99%
“…The PAMPTMA block of the copolymers is positively charged in aqueous solution, thus can electrostatically adsorb onto negatively charged surfaces such as silica. [44][45][46] This feature can be employed to produce stable polymer layers, which can be used in various practical applications, e.g., to prevent adhesion of biomolecules or conversely to promote specific attachment of cell types to surfaces. [47][48][49] Dynamic light scattering (DLS) is employed to inquire the thermo-responsive behavior and hydrodynamic size of the copolymers in bulk aqueous solution.…”
Section: Introductionmentioning
confidence: 99%